2018
DOI: 10.1242/jeb.174391
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of reactive oxygen species generation in heart mitochondria from anoxic turtles: the role of complex I S-nitrosation

Abstract: Freshwater turtles () are among the very few vertebrates capable of tolerating severe hypoxia and re-oxygenation without suffering from damage to the heart. As myocardial ischemia and reperfusion causes a burst of mitochondrial reactive oxygen species (ROS) in mammals, the question arises as to whether, and if so how, this ROS burst is prevented in the turtle heart. We find that heart mitochondria isolated from turtles acclimated to anoxia produce less ROS than mitochondria from normoxic turtles when consuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 61 publications
10
52
5
Order By: Relevance
“…Baseline flows were established that were similar to previous perfused heart studies (Bundgaard et al, 2018;Farrell et al, 1994;Joyce et al, 2016) and in vivo blood flow measurements Wang and Hicks, 1996) in this species. Under control conditions, there was a significant negative relationship between input pressure and cardiac output (R 2 =0.63, P=0.01; Fig.…”
Section: Smooth Muscle Contraction Decreases Cardiac Output In Perfussupporting
confidence: 58%
“…Baseline flows were established that were similar to previous perfused heart studies (Bundgaard et al, 2018;Farrell et al, 1994;Joyce et al, 2016) and in vivo blood flow measurements Wang and Hicks, 1996) in this species. Under control conditions, there was a significant negative relationship between input pressure and cardiac output (R 2 =0.63, P=0.01; Fig.…”
Section: Smooth Muscle Contraction Decreases Cardiac Output In Perfussupporting
confidence: 58%
“…Complex I may also be inhibited by excess GSH through glutathionylation [53] since NAC treatment results in an increase in GSH levels. Moreover, the suppression of Complex I activity could also be a result of S-nitrosation of Complex I by NO, which is an effective mechanism to prevent ROS formation, thus protecting the cells from oxidative stress [54,55]. We have previously shown that NAC treatment partially protected the oxidative modification of mitochondrial complexes and helped in preserving the mitochondrial function in HepG2 cells [56].…”
Section: Discussionmentioning
confidence: 99%
“…Adult red-eared sliders of both sex (Trachemys scripta elegans) kept in aquaria at the animal care facility at Zoophysiology, Aarhus University, were used for experiments. While fasted, the turtles were progressively acclimated to low temperature (5°C) followed by randomized exposure to either normoxic (N=5, 0.66±0.13 kg) (termed 'cold normoxia') or anoxic conditions (N=4, 0.64±0.07 kg) (termed 'cold anoxia') for 9 days, according to a previously described protocol (Bundgaard et al, 2018;Bundgaard et al, 2019;Jensen et al, 2014). A control group (N=5, 0.61±0.04 kg) of non-fasting turtles taken directly from the aquaria at 25°C was also included in the study (termed 'warm normoxia').…”
Section: Animalsmentioning
confidence: 99%
“…Turtles were killed as previously described (Bundgaard et al, 2018). In brief, an overdose of pentobarbital (50 mg kg −1 ) was given via the supravertebral venous sinus.…”
Section: Tissue Samplingmentioning
confidence: 99%
See 1 more Smart Citation